OPTIMASI FORMULASI FLAKES BERBASIS TEPUNG UBI CILEMBU TEPUNG TAPIOKA SERTA TEPUNG KACANG HIJAU - thomas gozaly (Department of Food Technology, Universitas Pasundan, Bandung, 2019)
The purpose this research is to determine the best formulation of Flakes have as a base Cilembu sweet potato flour, tapioca flour,and green bean flour making using the Design Expert Application with Design D-optimal method. This research was done within two phases. The preliminary phase is was to determine starch and carotenoid in Cilembu sweet potato flour. The main this research is determine the best formulation of Flakes The respon in this research are chemical responses (including protein content, fat content, fyber content, and water content), physical response (including water absorption, and wrecked time), and sensory response (including color, aroma, flavor, and texture). The Flakes is made from Cilembu sweet potato flour, tapioca flour,and green bean flour. The application provides 11 formulations and made 1 formulations optimal, which Cilembu sweet potato flour 27,73%, tapioca flour 14,99%, and green bean flour 12,29%, sugar 14%, salt 1%, and water 30%. The responses results are 8,87% for protein content, 0,38% for fat content, 3,96% for crude fyber contect, 3,5% for water content, 141,03% for water absorption, 15 minutes wrecked time, 4,7 for color attribute before add milk, 5,33 for color attribute after add milk, 5,47 for flavor attribute after add milk, 5,27 for aroma attribute after add milk, 4,57 for flavor texture after add milk.